2021
DOI: 10.1134/s0026893321050113
|View full text |Cite
|
Sign up to set email alerts
|

Plasmolipin and Its Role in Cell Processes

Abstract: The mechanisms involved in the origin and development of malignant and neurodegenerative diseases are an important area of modern biomedicine. A crucial task is to identify new molecular markers that are associated with rearrangements of intracellular signaling and can be used for prognosis and the development of effective treatment approaches. The proteolipid plasmolipin (PLLP) is a possible marker. PLLP is a main component of the myelin sheath and plays an important role in the development and normal functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…6 B) in SK-SN-SH cells. PLLP encodes the proteolipid plasmolipin, which is a main component of synaptic plasma membranes and myelin sheaths and is involved in intracellular transport and neurite growth [ 49 ]. We then observed that rs4558409-KO promoted all-trans retinoic acid (ATRA)-induced neural development (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 B) in SK-SN-SH cells. PLLP encodes the proteolipid plasmolipin, which is a main component of synaptic plasma membranes and myelin sheaths and is involved in intracellular transport and neurite growth [ 49 ]. We then observed that rs4558409-KO promoted all-trans retinoic acid (ATRA)-induced neural development (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our study validated the biological role of AShM transitions at the PLLP rs4558409 locus, leading to alterations in POU3F2 binding ability and contributing to the downregulation of PLLP , providing etiological implications for SCZ or BPD. PLLP encodes the proteolipid plasmolipin, which is a main component of synaptic plasma membranes and myelin sheaths and is involved in intracellular transport and neurite growth [ 49 ]. AShM transitions at the PLLP rs4558409 locus across PDC twin pairs reduced PLLP transcriptional activity through hydroxymethylation-mediated inhibition of active POU3F2 binding affinity at the active T allele of the rs4558409 (G/T) regulatory locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLLP was initially isolated from plasma membranes of bovine kidney plasma membrane [39] and was later characterized as a component of synaptic plasma membranes, myelin sheaths, and endocytic vesicles [4,40]. PLLP, which mostly distributes in subapical endosomes, is required for apical endocytosis and endosomal maturation [41,42], and acts in the recycling of apical proteins from sorting endosomes to the apical membrane (Figure 2D).…”
Section: The Pllp-cmtm8 Branchmentioning
confidence: 99%
“…A computational analysis of transcriptomic data showed MAL2 to be one of the strongest hub genes involved in signaling pathways in diabetes type 2 connected to tuberculosis and rheumatoid arthritis, although the contribution (if any) of MAL2 to the disease is unknown [57]. Altered PLLP expression has been related to a number of neurological diseases (e.g., schizophrenia, depressive disorder, and Alzheimer's disease), diabetes type 2, cornea degeneration, lung sarcoidosis, and hyperalphalipoproteinemia [40]. A number of transcriptome-wide meta-analyses aimed at identifying genes involved in hypertension detected MYADM as a candidate [58][59][60].…”
Section: Association With Non-cancerous Diseasesmentioning
confidence: 99%